Reflections on The Communist Manifesto from Third World Socialism - McKelvey, Charles (Sociološki pregled, 2018)
Drawing from the cognitional theory of Bernard Lonergan and from anticolonial movements, the paper maintains that universal understanding of social dynamics is approached through personal encounter with social movements of the dominated. Moreover, the paper sustains that Marx implicitly followed this method of cross-horizon encounter, thereby forging a signifcant advance in understanding. The paper points to the marginalization of Marx’s insights in Western universities and to the oversights of Western Marxism, stressing the signifcance of revolutionary political subjects that have emerged in the Tird World. To overcome its limitations, Western Marxists ought to engage in sustained personal encounter with popular Tird World revolutionary movements.
Keywords: university structures; Third World movements; Marxism; Lonergan; Marx